Purchasing Decisions Based on Consumer Trust in Halal Topical Cosmetic Products - Yulianingsih; Nandan Limakrisna; Hari Muharam (International Journal of Business and Applied Economics, 2023)
The research aims to analyze the influence of religiosity, the role of halal labels, and product quality on purchasing decisions through consumer trust. Types of descriptive and verification research. The population is female students at three Islamic-based universities in the city of Bogor. The research sample consisted of 524 respondents. The analysis technique uses Structural Equation Modeling (SEM) using the Listrel 8.72 software program. The research results show that religiosity, the role of halal labels and product quality influence purchasing decisions through consumer trust. Consumer trust is a full mediating variable, meaning that consumer purchasing decisions on halal topical cosmetics are not directly based on religiosity, the role of the halal label and product quality, but must be based on the level of consumer trust in the halal topical cosmetic product.